The importance of microbiological and parasitological safety and quality in vegetables (Research, Society and Development, 2021)
The aim of this study was a literature review of the current status and recent years of fresh foods such as vegetables, mostly lettuce and kale consumed in natura, emphasizing studies from journals published in the last 20 years considering the presence of microorganisms such as coliforms at 45 ºC, Salmonella ssp, and various fungi. The consumption of fresh foods in recent decades has increased considerably, due to the search for knowledge of the origin of the foods consumed, mainly in vegetables. In small towns, the cultivation and sale of vegetables and vegetables is mostly carried out by families in their small gardens, often outdoors and in the urban area itself, where there may be various risks for the production of these natural foods, such as septic tanks, open sewers and stray animals, for this reason, these plants are subject to contamination by opportunistic microorganisms, such as coliforms at 45 ºC, Salmonella ssp and fungi. Foodborne infections are common and termed foodborne illnesses. These diseases that can lead to death. It is concluded that food quality control is directly linked to health, that is, a product with quality and safety ensures that fewer outbreaks of foodborne diseases occur, substantially avoiding the burden on public health systems.